Tubo-ovarian abscess management in our clinic - Necdet Öncü; Ali Buhur; Hüseyin Güray Biçer (Ginekologia Polska)
OBJECTIVES: It is aimed to examine and determine the sociodemographic, clinical parameters and ultrasonographic (USG) findings and to make various predictions about patients who will need tube-ovarian abscess (TOA) surgery. MATERIAL AND METHODS: Within the scope of the study conducted between April 2016 and March 2021, 140 patients diagnosed with TOA were evaluated. The parties in the comparison were compared based on clinical and USG findings of demographic characteristics of the patients who received medical and surgical treatment and those who received only medical treatment. RESULTS: Ninety-eight (72.05%) patients whose surgical and medical treatment required underwent laparotomy, laparoscopy, and USG-guided drainage. The most important potential hazards for surgical procedures include severe abdominal pain, extent of abscess, and length of hospital stay. Critical threshold for a surgical procedure is when the abscess size becomes 5.5 cm (95% CI: 0.686–0.855, 0.686–0.855, p < 0.05). In the USG-guided drainage group no other complications were noticed. CONCLUSIONS: The size of the abscess is a valuable indicator of whether surgical treatment is required to manage TOAs and the USG-guided drainage led to fewer complications.